Peer observation of teaching: A decoupled process - Marty Chamberlain (Active Learning in Higher Education, 2011)
This article details the findings of research into the academic teaching staff experience of peer observation of their teaching practice. Peer observation is commonly used as a tool to enhance a teacher’s continuing professional development. Research participants acknowledged its ability to help develop their teaching practice, but they also reported that it could operate superficially as a tick box exercise, that its outcomes were frequently decoupled from formal staff development processes, and that its purpose and usefulness therefore seemed unclear. This article argues that the presence of decoupling reinforces the need to account for structural factors that can interact with peer observation of teaching to ensure it is a meaningful exercise for all teaching staff. It concludes that the published academic literature is perhaps guilty of overplaying the role of personal choice and individual tutor characteristics when addressing the complex issue that is staff disengagement with peer observation of teaching.